2022
DOI: 10.1007/s10792-022-02383-6
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of OCT parameters after intravitreal anti-VEGF inhibitors in neovascular AMD patients in a real-world setting

Abstract: Purpose The aim of the present study was to evaluate changes of best corrected visual acuity (BCVA), retinal nerve fiber layer thickness (RNFL), total macular volume (TMV), intraocular pressure (IOP) and central retinal thickness (CRT) after intravitreal injection of ranibizumab, bevacizumab and aflibercept in patients with neovascular age-related macular degeneration (nAMD) in a clinical real world setting. Methods In a retrospective clinical study design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Luke et al, analyzed OCT parameters (such as total macular volume, RNFL, and central retinal thickness) in 120 eyes treated with multiple intravitreal injections of ranibizumab, bevacizumab, and aflibercept due to neovascular AMD in a clinical real world setting study. They found out that RNFL remained constant over the course of 8 years [ 23 ]. Finally, meta-analysis conducted by Shin et al, found no association between anti-VEGF treatment and RNFL thickness changes in AMD patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Luke et al, analyzed OCT parameters (such as total macular volume, RNFL, and central retinal thickness) in 120 eyes treated with multiple intravitreal injections of ranibizumab, bevacizumab, and aflibercept due to neovascular AMD in a clinical real world setting study. They found out that RNFL remained constant over the course of 8 years [ 23 ]. Finally, meta-analysis conducted by Shin et al, found no association between anti-VEGF treatment and RNFL thickness changes in AMD patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%